"Global Research Trends and Collaborations on Christian Education Management: A Bibliometric Review" May Increase Its Academic Appeal - Ostinar Sitinjak (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of the study is that bibliometrics is important to review the existing literature on educational management in Christian religious education. Through this approach, it is expected to identify trends, knowledge gaps, and potential solutions that can be proposed as new innovations in improving the effectiveness of educational management in Christian religious education. This innovative solution is expected to be the foundation for the development of Christian religious education that is more holistic and relevant to the demands of the times. This study uses a bibliometric approach to describe and analyze literature related to Christian educational management. The research population includes all literature related to the database. The research sample is focused on the last 5 years (2020-2024) and only on journal articles. The data collection process begins with the identification stage using the keyword "Christian Education Management". The analysis was carried out using VOSviewer software to identify main topics, mark relationships between topics, and find research trends. The results of the study are presented in the form of tables, graphs, and narratives, which provide an overview of the landscape of Christian educational management research. The bibliometric analysis strategy is explicitly Co-occurrence, Co-authorship, Co-itation, Bibliographic couple. The selection of Dimension AI was made because this database has a wide coverage and open access, including literature that may not be indexed in Scopus or WoS. The results showed that despite the differences in numbers, the main topics and keywords were similar, indicating that Dimension AI is quite representative for the purpose of this study. Analysis using VOSviewer and Microsoft Excel showed significant fluctuations in the number of publications on Christian religious education management from 2020 to 2024, with the highest peak occurring in 2022, reflecting a positive trend in research interest in this field.